2020
DOI: 10.1002/hbm.24959
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss reduces head motion: Revisiting a major confound in neuroimaging

Abstract: Head motion during magnetic resonance imaging (MRI) induces image artifacts that affect virtually every brain measure. In parallel, cross-sectional observations indicate a correlation of head motion with age, psychiatric disease status and obesity, raising the possibility of a systematic artifact-induced bias in neuroimaging outcomes in these conditions, due to the differences in head motion. Yet, a causal link between obesity and head motion has not been tested in an experimental design. Here, weshow that a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 29 publications
2
14
1
Order By: Relevance
“…We also propose that our findings require replication in a larger sample as the number of participants in the different risk profile subgroups was small. It has recently been observed that head motions are more prominent in obese than normal weighted cohorts (Beyer et al, 2020). In the present study HARDI but not qMT data were corrected for motion artefacts.…”
Section: Discussionmentioning
confidence: 79%
“…We also propose that our findings require replication in a larger sample as the number of participants in the different risk profile subgroups was small. It has recently been observed that head motions are more prominent in obese than normal weighted cohorts (Beyer et al, 2020). In the present study HARDI but not qMT data were corrected for motion artefacts.…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, additionally controlling for head motion parameters in our statistical models increased the effect sizes in several networks but reduced effect sizes in the frontoparietal network. A prior study showed weight loss is related to reduced head motion, suggesting a need to assess head motion effects in obesity neuroimaging studies 127 . Further work is needed to identify mediating factors between head motion and body weight, and to determine how to optimally include head motion parameters in BMI/obesity neuroimaging.…”
Section: Discussionmentioning
confidence: 99%
“…Head motion was quantified using mean framewise displacement (mFD) according to Power et al, 2012 and log-transformed for further analysis (logmFD). As pre-registered, we did not exclude anybody based on high average head motion (Beyer et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Further, while higher BMI has been consistently associated with more head motion during rsfMRI (Beyer et al, 2017;Hodgson et al, 2016), previous studies in bariatric surgery patients have not taken this important confounder of FC into account. In the present sample, we previously reported a group-by-time interaction on head motion (Beyer et al, 2020). Thus, we aimed to rigorously control for motion-related variance in our analyses.…”
Section: Introductionmentioning
confidence: 95%